INSTITUTION ANALYSIS OF FARMERS GROUP HOLDERS OF SOCIAL FORESTRY LICENSE IN THE FOREST MANAGEMENT UNIT OF BATUTEGI, INDONESIA - Uma , Kaifa; Febryano, Indra Gumay; Wulandari , Christine; Kaskoyo, Hari; Darmawan, Arief; Fitriana , Yulia Rahma; Safe'i , Rahmat; Herwanti, Susni; Novriyanti, Novriyanti; Iswandaru , Dian (Forestry Study Program University Of Mataram, 2024)
Institutions are the rules of the game that can regulate the activities of Farmers Group members to support Social Forestry activities. The study aimed to analyze the structure, roles, and institutional rules of the Farmers Group of Karya Tani Mandiri and the Farmers Group of Karya Bakti in the Forest Management Unit of Batutegi, Indonesia. Data collection was carried out using interviews, observations, and literature studies. The data that has been collected is then analyzed using a Likert scale. The results showed that Farmers Group of Karya Bakti in terms of structure, roles, and complete game rules compared to Farmers Group Karya Tani Mandiri. This is because the Farmers Group of Karya Tani Mandiri at the time in the field did not have Memorandum of Association/Article of Association, Decree of the Regent, institution’s structure, the role of the structure, but the facts in the field Farmers Group of Karya Bakti violated the rules of the game in the Memorandum of Association/Article of Association, namely cutting down trees for personal gain. In forest areas, the application of the game rules to the institution's performance of the Farmers Group of Karya Tani Mandiri and the Farmers Group of Karya Bakti needs to be improved so that forest management can be sustainable by understanding and obeying the rules of the game that apply.